Assessment of Fertilizer Quality Available in Markets of Faisalabad Division, Pakistan: Fertilizer Quality in Faisalabad (Biological Sciences - PJSIR, 2023)
Even though multidimensional fertilizer quality regulation processes are there, availability of good quality fertilizer is still a challenge. Fake, adulterated and substandard fertilizers are present in the market and being sold. Soil and water testing laboratory for research, Faisalabad under the umbrella of Directorate of Soil Fertility Research Institute (SFRI), Lahore is working as legally authorised laboratory for fertilizer quality testing. A total of 3847 number of fertilizer samples having different compositions during the year 2014-15 to 2018-19 were sampled from the markets/warehouses in Faisalabad division by extension department. Out of 3847 analysed samples, 3636 (94.5%) were declared fit for crop use whereas the remaining 211 (5.5%) were found to be unfit. Out of total unfit samples maximum (40%) were reported from Faisalabad district followed by Thang and Toba Tek Singh. Least (8%) were reported from Chiniot district. It appears overall that 14.8% adulteration was found in micronutrients followed by miscellaneous category (humic acid, amino acid, bio organo phosphate) where percentage was noted as 14.4%. More than 30% of organic matter compositions received in laboratory were found adulterated. Among phosphorus fertilizers 11.4% single super phosphate (SSP) samples were reported below than the specified limit. 8.1% multinutrient fertilizers having nitrogen, phosphate, potassium (NPK) (liquid/solid), 2.6% sulphate of potash (SOP)/muriate of potash (MOP) and least 0.3% NP and nitrophos samples and none of the calcium ammonium nitrate (CAN) sample was found below the specified limit during the period of review.